Mechanical and Functional Properties of a Novel Apatite-Ionomer Cement for Prevention and Remineralization of Dental Caries - Imataki, Rie (Materials (Basel), 2019)
Especially in pediatric dentistry, prevention by the control of initial lesions prior to cavitation is very important, and application of a pit and fissure sealant is essential to achieve this. Numerous reports have suggested that resin-based sealants are inferior to sealants based on glass-ionomer cement (GIC), because of GIC’s many advantages, such as fluoride ion release properties and its good adhesion to tooth structures. However, the use of GIC is impeded due to its low flexural strength and fracture toughness. In this paper, we developed and characterized an apatite-ionomer cement (AIC) that incorporates hydroxyapatite (HAp) into the GIC; this development was aimed at not only reinforcing the flexural and compressive strength but also improving some functional properties for the creation of the material suitable for sealant. We examined the influence of differences in the compounding conditions of GIC powder, liquid, and HAp on flexural and compressive strengths, fracture toughness, fluoride ion release property, shear bond strength to bovine enamel, surface pH of setting cements, and acid buffer capability. These methods were aimed at elucidating the reaction mechanism of porous spherical-shaped HAp (HApS) in AIC. The following observations were deduced. (1) HAp can improve the mechanical strengths of AIC by strengthening the cement matrix. (2) The functional properties of AIC, such as acid buffer capability, improved by increasing the releasing amounts of various ions including fluoride ions. The novel AIC developed in this study is a clinically effective dental material for prevention and remineralization of tooth and initial carious lesion.